Chao Teri: The Traditional Fish Fermentation from South Sulawesi, Indonesia. Issue 1 (1st October 2022) - Syahriati,; Nur Fitriani, UA; Yusuf, Muhammad; Saleh, Rahmawati; Luthfiah,; Sumarni,
Abstract: Chao fish is a traditional product of the Bugis-Makassar ethnic, which is processed from anchovy fermentation. Chao teri production center is in Pangkep regency of South Sulawesi Province, especially in Liukang Topabiring and Labbakkang subdistricts. In this area, Chao fish is a complement to side dishes flavored with chilies and onions, and consumed with pickled mangoes and cucumbers. The fermentation process for approximately two weeks. Characteristics of fish Chao products are light brown or pink, slightly sour and salty taste, distinctive flavor, and has a paste-shaped texture. The descriptive qualitative and quantitative research method was used to explore processing techniques and volatile compounds in Chao teri. Observation and documentation were conducted to collect primary data. Instrumental analysis using Gas Chromatography-Mass Spectrometry with Solid Phase Micro-Extraction (GC-MS SPME) method is used to determine the volatile compounds. Chao teri can be made from anchovy and shrimp. Chemical characteristics of Chao teri after 2 weeks fermentation obtained pH 6.35, lactic acid 1.20%, and protein 21.15%. The results of the GC-MS SPME analysis produced 73 volatile compounds. The compounds are 31 hydrocarbons, 12 alcohols, 9 aldehydes, 8 ketones, 4 esters, 2 organic acids, 1 furan, and 6 other compounds. The dominant types of amino acids found in Chao teri products are glutamic acid, leucine, aspartic acid, and lysine. In this article, the origin of Chao teri, its method of processing, and the scientific perspectives are discussed.